(untitled) (Research, Society and Development, 2019)
This study sought to identify if there are difficulties encountered by nursing professionals during the Nursing Care Systematization to patients with breast cancer in an Inpatient and Oncology Sector / Chemotherapy Unit of a hospital in the interior of the state of Rio Grande do Sul. In this way the present study is classified as descriptive and exploratory that used as technical procedure the data survey in a cross-sectional form with qualitative approach. For that, an interview was applied to nine participants of the nursing team of the oncology and hospitalization sector. All participants in the study signed the Informed Consent Term. Responses were transcribed and analyzed according to approximations with the Bardin Content Analysis. The results of the present study pointed out that the work of nursing professionals in the oncology sector is repetitive and presents daily demands, making it unfeasible to perform the Systematization during the visits, restricting it to admission in the sector. The study serves as a contribution to understand how Nursing Care Systematization is performed in patients diagnosed with breast cancer by nursing professionals from an Oncology and Clinical sector. It can be noticed that the most important impacts reported by the nursing team are identified when an inpatient, concern about hair loss and fear of losing one or both breasts appears in most cases.